Analysis of nondegradable cyclins reveals distinct roles of the mitotic cyclins in Drosophila meiosis. - Bourouh, M.; Dhaliwal, R.; Rai, R.; Qureshi, H.; Swan, A. (G3 : genes - genomes - genetics, 2024)
Meiosis is a complex variant of the mitotic cell cycle, and as such relies on many of the same proteins involved in mitosis, but utilizes these in novel ways. As in mitosis, Cdk1 and its cyclin partners, Cyclin A, B, and B3 are required at multiple steps in meiosis. Here, we study the effect of stabilized forms of the three mitotic cyclins to study the consequences of failure to degrade the cyclins in meiosis. We find that stabilized Cyclin B3 promotes ectopic microtubule polymerization throughout the egg, dependent on APC/C activity and apparently due to the consequent destruction of Cyclin A and Cyclin B. We present data that suggests CycB, and possibly CycA, can also promote APC/C activity at specific stages of meiosis. We also present evidence that in meiosis APC/CCort and APC/CFzy are able to target Cyclin B via a novel degron. Overall, our findings highlight the distinct functions of the three mitotic Cdk-cyclin complexes in meiosis.